Tectonism and Its Relation to Magmatism Around Santorini Volcano From Upper Crustal P Wave Velocity. Issue 10 (16th October 2019) - Heath, B. A.; Hooft, E. E. E.; Toomey, D. R.; Papazachos, C. B.; Nomikou, P.; Paulatto, M.; Morgan, J. V.; Warner, M. R.
Abstract: At extensional volcanic arcs, faulting often acts to localize magmatism. Santorini is located on the extended continental crust of the Aegean microplate and is one of the most active volcanoes of the Hellenic arc, but the relationship between tectonism and magmatism remains poorly constrained. As part of the Plumbing Reservoirs Of The Earth Under Santorini experiment, seismic data were acquired across the Santorini caldera and the surrounding region using a dense amphibious array of >14, 300 marine sound sources and 156 short‐period seismometers, covering an area 120 km by 45 km. Here a P wave velocity model of the shallow, upper‐crustal structure (<3‐km depth), obtained using travel time tomography, is used to delineate fault zones, sedimentary basins, and tectono‐magmatic lineaments. Our interpretation of tectonic boundaries and regional faults are consistent with prior geophysical studies, including the location of basin margins and E‐W oriented basement faults within the Christiana Basin west of Santorini. Reduced seismic velocities within the basement east of Santorini, near the Anydros and Anafi Basins, are coincident with a region of extensive NE‐SW faulting and active seismicity. The structural differences between the eastern and western sides of Santorini are in agreement with previously proposed models of regional tectonic evolution. Additionally, we find that regional magmatism has been localized in NE‐SW trending basin‐like structures that connect the Christiana, Santorini, and Kolumbo volcanic centers. At Santorini itself, we find that magmatism has been localized along NE‐SW trending lineaments that are subparallel to dikes, active faults, and regional volcanic chains. These results show strong interaction between magmatism and active deformation. Key Points: P wave tomography of the upper crust (<3 km) around Santorini delineates basin structures including buried margins and basement faults These structures, also seen in seismic reflection images, result from both the integrated tectonic history, as well as ongoing deformation Tectonic structures and stresses localize volcanism in regional NE‐SW basins, and, within Santorini caldera, along local NE‐SW lineaments